Retiring intentions: The role of conflicts with the boss and health status as a moderator - Martha Ottenbacher (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2016)
This paper considers an employee's retirement intentions and its influencing factors. The role of conflicts that an employee experiences with his/her boss and the role of his/her health status are analyzed using Socio-Economic Panel (SOEP) data. Estimation results show that conflicts matter as well as an individual's health status when considering the probability of retirement. Having conflict with the boss rises the probability of retiring intentions significantly, even after accounting for a wide set of controls. Employees in good health have fewer intentions to retire. Split into subgroups, there appears to be a slight but notable moderating role of health status: Among healthy employees conflict with the boss raises retirement intentions even more. This suggests that healthy people (compared to unhealthy people) may well be able to continue working but not necessarily do so because social factors - namely conflict with the boss - become more important.
Keywords: J26; J29; I12; M54; 330; conflicts with the boss; retirement intentions; health status